Rattus remotus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Rattus remotus (Robinson and Kloss, 1914). Ann. Mag. Nat. Hist., ser. 8, 18:231. TYPE LOCALITY: Thailand, Koh Samui. DISTRIBUTION: Phangan, Tao, and Samui Isis. (Thailand). COMMENT: Considered a subspecies of muelleri by Hill, 1960, Bull. Raffles Mus., 29:1 -112, and as a subspecies of annandalei by Chasen, 1940; but see Marshall, 1977, in Lekagul and McNeely, p. 469. Conspecific with sikkimensis (GGM). Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 5), pp. 504-560 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 553, DOI: 10.5281/zenodo.7353037